EFFECTIVENESS OF THE ACCELERATED STUNTING REDUCTION PROGRAM THROUGH CONVERGENCE ACTION IN NORTH LAMPUNG REGENCY - Kofa, Fadhila; Virgawenda, Tina Miniawati Barusman; Defrizal, Defrizal (Program Studi Magister Manajemen, 2024)
The purpose of this study is to evaluate the effectiveness of the stunting reduction acceleration program through convergence actions and to identify the supporting and inhibiting factors that influence its success in North Lampung Regency. The findings of this research are expected to provide recommendations for improving the program’s implementation. Supporting factors can be maintained and strengthened, while inhibiting factors need to be addressed with appropriate solutions so that the program can be carried out with better quality and sustainability. This research employed a descriptive qualitative approach, with data collected through interviews with 15 informants as well as document reviews from relevant institutions. The measurement of effectiveness was conducted using three approaches: input effectiveness, process effectiveness (covering planning, implementation, and evaluation), and output effectiveness. Based on these approaches, the study concludes that the acceleration program for stunting reduction through convergence actions in North Lampung Regency in 2023 has not yet achieved effective outcomes. This is due to limited understanding among program implementers regarding convergence-based stunting reduction strategies, as well as insufficient optimization of funding sources, particularly from the private sector.